CCR2 deficiency in monocytes impairs angiogenesis and functional recovery after ischemic stroke in mice. Issue 1 (December 2020) - Pedragosa, Jordi; Miró-Mur, Francesc; Otxoa-de-Amezaga, Amaia; Justicia, Carles; Ruíz-Jaén, Francisca; Ponsaerts, Peter; Pasparakis, Manolis; Planas, Anna M
Inflammatory Ly6C hi CCR2 + monocytes infiltrate the brain after stroke but their functions are not entirely clear. We report that CCR2 + monocytes and CCR2 + lymphocytes infiltrate the brain after permanent ischemia. To underscore the role of CCR2 + monocytes, we generated mice with selective CCR2 deletion in monocytes. One day post-ischemia, these mice showed less infiltrating monocytes and reduced expression of pro-inflammatory cytokines, markers of alternatively macrophage activation, and angiogenesis. Accordingly, Ly6C hi monocytes sorted from the brain of wild type mice 24 h post-ischemia expressed pro-inflammatory genes, M2 genes, and pro-angiogenic genes. Flow cytometry showed heterogeneous phenotypes within the infiltrating Ly6C hi CCR2 + monocytes, including a subgroup of Arginase-1 + cells. Mice with CCR2-deficient monocytes displayed a delayed inflammatory rebound 15 days post-ischemia that was not found in wild type mice. Furthermore, they showed reduced angiogenesis and worse behavioral performance. Administration of CCR2 +/+ bone-marrow monocytes to mice with CCR2-deficient monocytes did not improve the behavioral performance suggesting that immature bone-marrow monocytes lack pro-reparative functions. The results show that CCR2 + monocytes contribute to acute post-ischemic inflammation and participate in functional recovery. The study unravels heterogeneity in the population of CCR2 + monocytes infiltrating the ischemic brain and suggests that pro-reparative monocyte subsets promote functional recovery after ischemic stroke.